Teachers' Main Challenges Encountered During the Online Lessons After the Closure of Schools Due to the Covid-19 Pandemic - Azizova, Narmin; Dadashova, Nazrin (ADA University, 2020)
The pandemic, which struck the entire world , prompted changes in teaching and learning process which required new approaches. Most of the world's enrolled students are unable to attend school in person due to Covid-19-related school closures. In Azerbaijan, there aren't adequate study on the issues that teachers face while teaching online. Our research study investigates a novel topic in the field of Azerbaijani educational research. The goal of the research is to learn about the major obstacles that public school teachers faced and how principals helped them throughout the school closures. The issues that teachers encountered in one public school in Baku and two public schools in separate regions are examined in this study. The researchers conducted interviews with teachers to learn about the kind of obstacles they faced, as well as the sources of assistance they received from their principals. The findings of this study show that teachers had access to the internet, on the other hand , cheating, parental assistance were frequent. Teaching challenges were also common, such as teachers lack ICT skills, digital equipment, direct interaction with students, and increased in teachers' workload. Furthermore, teachers received support from administrators in a variety of ways, including observing online lessons, organizing training, technical support, emotional support, connecting with third parties, and using alternative technologies and planning meetings for teaching reasons, according to the research. The findings of this study highlight the need for more research into teachers' main challenges while teaching online lessons after school closure during to the Covid-19 pandemic locked down , in order to give more empirical evidence for the ministry of education and other stakeholders in the field of education.
Keywords: Online teaching.; Online education.; Education -- COVID19.; Education